2020
DOI: 10.1109/access.2020.2983917
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Seizure Detection With a Reduced Montage: A Way Forward for Ambulatory EEG Devices

Abstract: Electroencephalogram (EEG) is one of the fundamental tools for analyzing the behavior of brain and particularly helpful for treatment of epilepsy and detection of associated seizures. For longterm recording of EEG signals, current research is heading towards simple, unobtrusive and ambulatory devices with a small number of channels. The primary contribution of this paper is to assess the performance difference between the seizure detection results using features from all channels versus only the channels in/ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Firstly, traditional EEG caps have 16-32 channels, providing full coverage of the scalp. Hence, it must be understood if it is possible to effectively detect seizures with a reduced electrode set, to be placed into minimally intrusive devices, such as glasses or behind-the-ear systems [3]- [6]. The second challenge is linked to the performance of the system, especially for what concerns specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, traditional EEG caps have 16-32 channels, providing full coverage of the scalp. Hence, it must be understood if it is possible to effectively detect seizures with a reduced electrode set, to be placed into minimally intrusive devices, such as glasses or behind-the-ear systems [3]- [6]. The second challenge is linked to the performance of the system, especially for what concerns specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been suggested patient-specific deep learning-based automated seizure detection approaches using the CHB-MIT dataset ( 21 , 34 , 35 , 37–48 ). In terms of seizure detection with a full montage setting, Xu et al ( 44 ) proposed seizure detectors based on a three-dimensional (3D) CNN using time-frequency matrices by multiscale short-time Fourier transform with an average sensitivity, FAR, and latency of 94.95%, 0.08/h, and 2.3 s, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[3], has shown great potential in capturing elusive seizures outside clinical settings. However, the presence of motion artifacts, resulting from the patient's movement during recording, poses a significant challenge to reliable seizure detection using ambulatory EEG [4]. Recent progress in low-energy wireless transmission, sensor design and cost-effective hardware design has facilitated the creation of innovative wireless headsets, ideal for mobile EEG recording.…”
Section: Introductionmentioning
confidence: 99%